High Burden of Associated Injuries Occurring With Major Fractures of the Talus. (March 2020) - Ibrahim, Ishaq O.; Ye, Michael Y.; Jacobs, Jennifer; Smith, Jeremy T.; Kwon, John Y.; Miller, Christopher P.
Background: Talus fractures are severe injuries typically occurring after high-energy trauma. As a result, associated injuries to different anatomic sites and organ systems occur with high frequency. The objective of this study was to determine what injuries occur with high incidence in patients presenting with major fractures of the talus and to identify clinical injury patterns that may warrant special attention in these patients. Methods: We performed a retrospective review of patients presenting to 3 level 1 trauma centers with fractures of the talar neck, body, or head over a 14-year period. Patient charts were reviewed for associated orthopedic and nonorthopedic injuries identified during the initial patient encounter and hospitalization. Results: In total, 262 fractures in 258 unique patients met criteria for inclusion. Overall, 33.3% of talus fractures occurred in isolation. One or more associated injuries were identified in the remainder of cases (66.7%). The incidence of associated injuries was similar across fracture patterns. Mean total number of injuries per patient was 2.2 (range, 0-15). The ipsilateral foot was the most frequent site of associated orthopedic injury. Noncontiguous injuries occurred in 36% of cases. Lumbar spine injury occurred in 10.5% of cases. Lower extremity vascular injury was uncommon but bore significant association with open talus fractures. Conclusion: Talus fractures are commonly associated with injuries to different anatomic sites and organ systems. A similar rate of lumbar spine trauma may occur with major talus fractures as has been historically associated with calcaneal fractures. Thorough evaluation and a high index of suspicion are necessary when evaluating patients with major fractures of the talus to avoid missing concomitant injuries. Level of Evidence: Level IV, retrospective case series.